Methylphenidate improves executive functions in patients with traumatic brain injuries: a feasibility trial via the idiographic approach - Samir Al-Adawi (711559) (2020)
Background Road traffic accidents are known to be the main cause of traumatic brain injury (TBI). TBI is also a leading cause of death and disability. This study, by means of the idiographic approach (single-case experimental designs using multiple-baseline designs), has examined whether methylphenidate (MPH - trade name Ritalin) had a differential effect on cognitive measures among patients with TBI with the sequel of acute and chronic post-concussion syndromes. The effect on gender was also explored. Methods In comparison with healthy controls, patients with TBI (acute and chronic) and accompanying mild cognitive impairment (MCI) were screened for their integrity of executive functioning. Twenty-four patients exhibiting executive dysfunction (ED) were then instituted with the pharmacological intervention methylphenidate (MPH). The methylphenidate was administered using an uncontrolled, open label design. Results The administration of methylphenidate impacted ED in the TBI group but had no effect on mood. Attenuation of ED was more apparent in the chronic phases of TBI. The effect on gender was not statistically significant with regard to the observed changes. Conclusions To our knowledge, this is the first feasibility trial from the Arabian Gulf to report the performance of a TBI population with mild cognitive impairment according to the IQCODE Arabic version. This investigation confirms anecdotal observations of methylphenidate having the potential to attenuate cognitive impairment; particularly those functions that are critically involved in the integrity of executive functioning. The present feasibility trial should be followed by nomothetic studies such as those that adhere to the protocol of the randomized controlled trial. This evidence-based research is the foundation for intervention and future resource allocation by policy- or public health decision-makers. Other Information Published in: BMC Neurology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s12883-020-01663-x